2017
DOI: 10.21276/apalm.1207
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of Sinonasal Masses

Abstract: Background: Sinonasal mass is a common finding in the Otorhinolaryngology Department. These can be non-neoplastic or neoplastic. Nasal obstruction is the most common clinical presentation. Imaging studies are not always conclusive in these cases. So, the present study aimed at clinical presentation and histopathological classification of sinonasal masses.for histopathological examination and were stained by Hematoxylin and Eosin stain. Special stains were used wherever required. Immunohistochemistry was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 10 publications
11
15
0
Order By: Relevance
“…Similar findings of male preponderance were observed in studies conducted by Tondon et al, 10 Khan et al 11 and Kulkarni et al 6 We observed higher frequency of non-neoplastic lesions (80.33%) in comparison with neoplastic lesions (19.67%). Our findings are in concordance with Khan et al, 11 Kulkarni et al 6 and Mane et al 9 However Dasgupta et al 12 recorded an almost equal proportion of neoplastic and non-neoplastic lesions. (Table 5)…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar findings of male preponderance were observed in studies conducted by Tondon et al, 10 Khan et al 11 and Kulkarni et al 6 We observed higher frequency of non-neoplastic lesions (80.33%) in comparison with neoplastic lesions (19.67%). Our findings are in concordance with Khan et al, 11 Kulkarni et al 6 and Mane et al 9 However Dasgupta et al 12 recorded an almost equal proportion of neoplastic and non-neoplastic lesions. (Table 5)…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, benign neoplastic lesions (54.17%) marginally outnumbered the malignant neoplastic lesions (45.83%). Similar findings were noted in the study by Khan et al 11 But Tondon et al 10 and Mane et al 9 reported a higher proportion of benign neoplastic lesions (73.53% and 71.43% respectively) compared to malignant lesions (26.47% and 28.57% respectively).…”
Section: Neoplastic Lesions Of Sinonasal Tractsupporting
confidence: 86%
See 3 more Smart Citations